Research on the engine combustion characteristics of a free-piston diesel engine linear generator. (15th July 2018) - Zhang, Ziwei; Guo, Chendong; Song, Yu; Feng, Huihua; Zuo, Zhengxing; Jia, Boru; Roskilly, A.P.
Highlights: A continuous operating FPDLG is developed. A one-stroke starting strategy is proposed and applied on prototype successfully. Detailed studying of combustion characteristics of FPDLG is presented. The cyclical variation of prototype is discussed based on experimental results. Abstract: The free-piston diesel engine linear generator (FPDLG) shows a great deal of merits due to its unique structure and operation characteristics. For this reason, most researchers mainly investigated on the FPDLG characteristics. However, there has not been any report on the engine operation characteristics. So this paper focuses on the engine operation characteristics of the FPDLG during the generating process. According to the experimental results, it is found that the output power of the designed prototype can reach 5.16 kW with the thermal efficiency of up to 38.5%. Experimental test results are obtained and processed both in time and crank-angle coordinates. Compared to the conventional diesel engines, the ignition delay of the FPDLG is shorter and the premix combustion quality is better. By analyzing the operating cyclical variations of the prototype, the coefficient of variation (COV) of the compression ratio is found to be higher than 27%. While the peak in-cylinder gas pressure and pressure rising ratio cyclical variation can maintain a stable operation (similar to the conventional diesel engines), higher COVs of the compression ratio can always complicates the engine combustion. Therefore proper control strategies are necessary for the FPDLG.